2017
DOI: 10.1007/s11575-017-0336-9
|View full text |Cite
|
Sign up to set email alerts
|

The Embedding of Transnational Entrepreneurs in Diaspora Networks: Leveraging the Assets of Foreignness

Abstract: The Strathprints institutional repository (https://strathprints.strath.ac.uk) is a digital archive of University of Strathclyde research outputs. It has been developed to disseminate open access research outputs, expose data about those outputs, and enable the management and persistent access to Strathclyde's intellectual output. Abstract In this paper we examine how foreign actors capitalize on their ethnic identity to gain skills and capabilities that enable them to operate in a new and strange environment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 93 publications
3
26
0
Order By: Relevance
“…Critical labour market barriers, access to resources from various sources, and targeted clientele (Ley 2006;Deakins et al 2009;Kitching et al 2009) characterise ethnic and/or migrant entrepreneurs' distinctiveness from other host-country entrepreneurs (Engelen 2001;Rusinovic 2008aRusinovic , 2008bDeakins et al 2009). The role of co-ethnics is critical (Light and Bonacich 1991;Waldinger 1993;Dana 1997;Zhou 2004;Deakins et al 2005;Dana and Morris 2007;Light and Dana 2013;Stoyanov et al forthcoming), particularly as they are targeted as clients and enable access to resources (Light 1984;Ward and Jenkins 1984;Portes 1998;Davidsson and Honig 2003;Deakins et al 2007;Sepulveda et al 2011;Rumbaut and Portes 2014). Indeed, most (but not all) ethnic entrepreneurs do not access resources through formal sources of support and advice (Smallbone et al 2003;Deakins et al 2005).…”
Section: The Niche Market Of Ethnic Entrepreneurs and Breakoutmentioning
confidence: 99%
“…Critical labour market barriers, access to resources from various sources, and targeted clientele (Ley 2006;Deakins et al 2009;Kitching et al 2009) characterise ethnic and/or migrant entrepreneurs' distinctiveness from other host-country entrepreneurs (Engelen 2001;Rusinovic 2008aRusinovic , 2008bDeakins et al 2009). The role of co-ethnics is critical (Light and Bonacich 1991;Waldinger 1993;Dana 1997;Zhou 2004;Deakins et al 2005;Dana and Morris 2007;Light and Dana 2013;Stoyanov et al forthcoming), particularly as they are targeted as clients and enable access to resources (Light 1984;Ward and Jenkins 1984;Portes 1998;Davidsson and Honig 2003;Deakins et al 2007;Sepulveda et al 2011;Rumbaut and Portes 2014). Indeed, most (but not all) ethnic entrepreneurs do not access resources through formal sources of support and advice (Smallbone et al 2003;Deakins et al 2005).…”
Section: The Niche Market Of Ethnic Entrepreneurs and Breakoutmentioning
confidence: 99%
“…A great deal of research in entrepreneurship has demonstrated that immigrant and diaspora entrepreneurs contribute substantially not only to their countries of origin's small and medium enterprises (SMEs) development but also their host countries' economies (Chand, 2016;Chrysostome, 2014;Newland and Tanaka, 2010;Riddle and Brinkerhoff, 2011;Stoyanov, Woodward and Stoyanova, 2018b). In particular, diaspora entrepreneurs contribute to job creation, foreign currency inflows and economic growth in their countries of origin (Brinkerhoff, 2016;Coniglio and Brzozowski, 2016;Riddle and Brinkerhoff, 2011;Riddle, Hrivnak and Nielsen, 2010;Mani 2004) and develop self-employed businesses, SMEs and niche market products in their countries of residence (Crick and Chaudhry, 2013;Jones, Ram, Edwards, Kiselinchev and Muchenje, 2014;Smallbone, Bertotti and Ekanem, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…2013; Stoyanov et al . 2018) (21 articles in this review). Others even link identity to venture success, for example by showing the effects of family nurturer and entrepreneurial identities (Miller et al .…”
Section: Future Directions In Ioe Researchmentioning
confidence: 98%